PERLINDUNGAN PATEN BAGI PEMOHON ASING ATAS INVENSINYA - Pratiwi Citra Kurnia Wilujeng; Djumadi; Yulia Qamariyanti (The Juris, 2023)
The objectives to be achieved in the writing of the thesis are to analyze and criticize patent protection against foreign inventions in laws and regulations and to analyze and criticize the juridical consequences for patent applicants as well as how to apply for patents abroad, procedures and patent registration flows. In writing this thesis, the author uses research with a type of normative legal research with the nature of research, namely prescriby of a study that aims to get suggestions on what to do to overcome certain problems. Legal materials in the form of primary and secondary legal materials obtained from literature studies. Processing and analysis of legal materials is carried out by analyzing deductive to inductive legal materials. From the results of the study there is a conclusion that is. First. The existence of patent protection for foreign inventions to provide a sense of comfort, security and increase foreign investors investing in Indonesia. As well as to increase economic growth, open jobs for people in Indonesia and open new areas that were initially isolated into open, developing, developed and increasing foreign inventions. Second. Juridical consequences for foreign applicants with some changes to the applicable regulations aimed at opening up broad employment for the people of Indonesia.